Evaluation of the utility of popliteal lymph node examination in a cyclophosphamide model of immunotoxicity in the rat. (3rd July 2016) - Lapointe, Jean-Martin; Valdez, Reginald A.; Ryan, Anne M.; Haley, Patrick J.
Abstract: The objective of this study was to characterize the variability of rat lymphoid organ weights and morphology following treatment with a known immunotoxicant, with a focus on the usefulness of evaluating popliteal lymph node weight and histology. Cyclophosphamide was administered to male Sprague-Dawley rats by oral gavage at doses of 2, 7 or 12 mg/kg/day for 10 consecutive days. Left and right popliteal lymph nodes (PLN), spleen and thymus were collected at necropsy, weighed, fixed and processed for histopathology. Femoral bone marrow was also collected, fixed and processed for histology. Organ weight variability was greater for PLN than for either spleen or thymus in control animals. There was a significant but weak correlation between paired left and right PLN weights ( p  < 0.005; r 2  = 0.2774). Significant treatment-related decreases in lymphoid organ weights were observed in spleen and thymus at ≥ 7 mg/kg/day ( p  < 0.01), whereas in PLN a significant decrease ( p  < 0.05) was noted only at 12 mg/kg/day. The inclusion of PLN did not enhance the sensitivity of detection of systemic treatment-related changes in lymphoid organs in a rat cyclophosphamide model.